RETRACTED ARTICLE: Assessment of the benefits of 3D printing of advanced thermosetting composites using process simulation and numerical optimisation - Struzziero, Giacomo; Barbezat, Michel; Skordos, Alexandros A. (Elsevier, 2023)
3D printing of continuous fibre reinforced thermosetting matrix composites is set to revolutionise composite manufacturing practice. The potential of curing additively is anticipated to bring significant improvement in terms of increasing process speed, producing geometries that are inaccessible with current processing routes and eliminating detrimental exothermic effects during the process. This study presents a comparison between the curing stage of the 3D printing and standard batch processing for carbon fibre/epoxy components of varying thickness and size. An optimisation methodology links simulation of the cure using Finite Element solver Abaqus with a Genetic Algorithm capable of dealing with multi-objective problems. Optimal cure cycles to minimise both process time and temperature overshoot in 3D printing and batch processing are identified and the optimal trade-offs compared. The results highlight that temperature overshoot reduction up to 85 % is possible and that the intrinsic additive nature of the 3D printing allows eliminating the dependence of temperature overshoot on thicknesses and producing components with thicknesses that are very difficult to manufacture conventionally. A simplified procedure for the estimation of 3D printing process duration is proposed based on the results of finite element simulation. This is used for exploration of the limits of the process with respect to part size and for a generic comparison of process applicability against batch processing. The analysis shows that 3D printing is highly advantageous for small components, is efficient for mid-size components and can – on the basis of its scalability – offer a feasible route for producing large and very large components.
This article was retracted on 12 December 2022 details can be found on the publishers site at: https://doi.org/10.1016/j.addma.2022.103353
Keywords: Thermosetting resin; 3D printing; Continuous fibres; thick composites